IMPACT OF VARYING FIBER INTAKE AND PARTICLE SIZE ON THE PROPORTION OF FAT DEPOTS AND THE FATTY ACID PROFILE IN NAIMI LAMBS - Abdulkareem M. Matar; Riyadh S. Aljumaah; Ahmed A.K. Salama; Faisal A. Alshamiry; Ramzi A. Amran; Muttaseem M. Abdulrahman (Journal of Animal and Plant Sciences, 2025)
The Naimi sheep is one of the main breeds in Saudi Arabia, characterized by a thick tail and substantial fat deposits around the intestines. This study aimed to evaluate the influence of fiber type (alfalfa hay vs. wheat straw) and feed particle size (FPS) on the rate of fat deposition in in three major internal depots: tail fat (FT), omental fat (OF), and kidney knob channel fat (KKCF). Thirty-six weaned male Naimi lambs were divided into four treatments of 9 lambs each. At the end of the feeding trial, lambs were slaughtered and their internal fat depots removed to measure fat volume and fatty acid (FA) profiles. Lambs fed small sized wheat straw (WS2), had the lowest carcass fat weight (23.65 kg), whereas lambs fed uncrushed wheat straw (WS1) and uncrushed alfalfa hay (AH1) showed the highest fat percentages (WS1: 30.23 %; AH1: 28.92 %). Feeding hay alfalfa as a source of fiber to lambs had a significant effect on the levels of omega-3 (n-3) and α- linoleic acid (ALA) levels in in FT, OF and, KKCF. Conversely, WS1 increased the levels of stearic acid and odd-chain fatty acid (OCFA). In contrast, the feed with small sizes as AH2 and WS2 significantly elevated linolenic acid (LA), total polyunsaturated fatty acids (PUFA) and Omega 6 (n-6) in all three depots. Quality indices revealed that lambs fed alfalfa hay and wheat straw had lower atherogenicity index (AI) and thrombogenicity index (TI) indices in the fat tail compared to OF and KKCF. Moreover, the high ratio of hypercholesterolemic FA (hFA) to hypocholesterolmic FA (HFA) resulted in better values for fat tail (1.50), omental fat (1.01) and KKCF (1.26), which do not indicate any risk for human health. Thus, both the source and size of fiber particles had a significant influence on total fat deposition and FA profiles in lambs. Feeding strategies can be tailored by adjusting fiber source and particle size to modulate ruminal volatile fatty acid (VFA) and internal fat deposition.
Keywords: Naimi lambs; fatty acid profile; Omental fat; kidney knob channel fat; fat tail; fiber type; fiber particles size